Pengaruh Komunitas Virtual Terhadap Keputusan Pembelian Skincare Skintific : Survei Pada Komunitas Virtual @Ohmybeautybank Di Twitter - Andini Desti Nur Rahmadina; Oktaviana Purnamasari (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
The growing technology in this digital age makes it easier for consumers to access information. When consumers want to buy goods from a brand like Skincare, consumers can access a virtual community related to skincare or beauty. Objectives of this study 1). Know the virtual community of Oh My Beauty Bank on Twitter at Skincare Skintific. 2). Knowing the purchasing decisions of Twitter followers @ohmybeautybank against skincare products Skintific 3). Measuring the virtual communities of Oh My Beauty Bank against Skintific skincare purchase decisions. The theories used in this research are virtual community theory (composition and activity, social organization, language and interaction, culture, and identity) and the theory of purchase decisions. (Problem Recognition, Information Search, Alternative Evaluation, Purchase Decision, and Post-Purchase Evaluation). The study used a quantitative approach with a survey method, distributing questionnaires to 81 respondents. The virtual community has an average result of 2.96 with agreed-upon answers. 2). Purchasing decisions have an average outcome of 3.2 with agreeing answers. 3). The virtual community Oh My Beauty Bank has an influence on purchase decisions of 72.5%, while the other 27.5% comes from other factors outside the research variable.